The Effectiveness of Fertilizer Subsidy: How the Impact to the Production - Adiraputra, Prasaktiyoga; Supyandi, Dika (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
A lot of budgets had spent by the government on fertilizer subsidies. However, in its implementation there were still many obstacles. Therefore, the effectiveness of subsidies and their impact on production was interesting to study. The aim of this research was to describe the effectiveness of fertilizer subsidies and to determine the impact of the effectiveness of fertilizer subsidies on rice production. This research was conducted in Sukaasih Village, Sukatani Sub-district, Bekasi Regency. The research sample was determined by the multistage sampling method which resulted 109 farmers samples. The data that had been obtained were analyzed using frequency distribution analysis and multiple linear regression. The results showed that the implementation of fertilizer subsidies in Sukaasih Village was not effective. Variables that affected rice production were land area, the use of NPK fertilizer, SP-36, the use of seeds, and the effectiveness of fertilizer subsidies. Therefore, the government needs to tighten the target and application of subsidized fertilizers by collaborating with related parties so that subsidized fertilizers can be effective, on target, and efficient because the effectiveness of subsidized fertilizers affected rice production.